Juvenile Delinquency and Culture Conflict - Irene, W (My University, 1966)
The study involves surveys of two areas* one delinquent and the other non-delinquent* The areas were decided on in consult tion * i t h the A* S, P. of the Peilyagoda Police* The delinquent area i e witt i n the Peliyugoda Urban Council Limits i n the South Alutnkurukorale* The non-delinquent area i e the V i l l a g e of Biya^aaa within the Narassnala V i l l a g e Committee Lin:its i n the Siyane Korale Adikarapattu,